The Influence of Transformational and Democratic Leadership Styles on The Quality of Administrative Services Mediated by Technology Utilization - S. Susanti; Yana Fajriah; Rezki Arianty Akob (Golden Ratio of Mapping Idea and Literature Format, 2025)
This study aims to analyze the influence of transformational and democratic leadership styles on the quality of administrative services with technology utilization as a mediating variable at the Faculty of Engineering, Hasanuddin University. Primary data were collected through questionnaires distributed to respondents. The population of this study consists of all students of the Faculty of Engineering, Hasanuddin University. To determine a representative sample size, the Slovin formula was applied, resulting in 384 respondents. This research employed a quantitative approach with a survey method, and the data were analyzed using Structural Equation Modeling (SEM) with AMOS software. The findings reveal that transformational leadership does not have a significant direct effect on the quality of administrative services, whereas democratic leadership has a positive and significant effect. Both transformational and democratic leadership styles significantly influence technology utilization, which in turn positively affects the quality of administrative services. Furthermore, technology utilization serves as a significant mediator in the relationship between both leadership styles and the quality of administrative services. These findings underscore the importance of integrating participative and transformational leadership with technology utilization to enhance the quality of administrative services in higher education institutions.